Local fractional integral transforms and their applications - Yang, Xiao-Jun (Mathematician); Baleanu, D. (Dumitru); Srivastava, H. M. (Amsterdam : Academic Press, 2015)
Annotation The methods of integral transforms via local fractional calculus have been used to solve various local fractional ordinary and local fractional partial differential equations, and also to figure out the presence of the fractal phenomenon. This book presents the basics of the local fractional derivative operators and investigates some new results in the area of local integral transforms.
CIP data; item not viewed.
Includes bibliographical references and index.
Keywords: Integral transforms; Fractional calculus; MATHEMATICS -- Calculus; MATHEMATICS -- Mathematical Analysis; Fractional calculus; Integral transforms; Electronic books; Electronic books